Microbial community composition and their activity against Phytophthora nicotianae at different growth stages of tobacco - Meng-yu Zhang; Han Li; Pu Miao; Hui Wang; Min Xu; Jian-xin Yang; Jin-yan Yang; Ye-bin Kang (Egyptian Journal of Biological Pest Control)
Abstract Background Tobacco, an economically significant crop, faces substantial losses due to infections by Phytophthora nicotianae. This study investigated the endophytic microbial community composition in tobacco plants across different growth stages and plant parts to identify endophytes that can antagonize P. nicotianae. Using high-throughput 16S/18S sequencing to detect endophytic bacteria and endophytic fungi in tobacco, the endophytic communities of roots, stems, and leaves during the vigorous and mature growth stages were analyzed. Pure culture methods isolated endophytes, and their antagonistic activity against P. nicotianae was assessed through inhibitory assays. Results Non-significant differences in richness indices (ACE and Chao1) and diversity index (Shannon) among roots, stems, and leaves at the same growth stage were found. However, significant differences in richness indices were observed between growth stages, though the diversity index remained consistent. During the vigorous stage, fungal communities were dominated by Fusarium and Acremonium, and bacterial communities by Burkholderia and Bradyrhizobium. In the mature stage, fungal communities shifted to Trametes, Penicillium, and Candida, while bacterial communities were dominated by Halomonas and Actinobacteria. Out of 52 fungal isolates, 14 showed antagonistic activity against P. nicotianae, with two isolates demonstrating over 50% inhibitory activity. Among 206 bacterial isolates, 23 exhibited antagonistic activity, with 12 showing over 60% inhibitory activity. Conclusions These findings highlight the variation in endophytic microbial communities with growth stages and their potential in biocontrol of P. nicotianae, providing a basis for developing new biocontrol strategies and advancing tobacco disease management technologies.